Counting of lactic bacteria in yogurts and dairy drinks in the metropolitan region of Recife-PE (Research, Society and Development, 2022)
Fermented milk-based products, such as fermented dairy drinks and yogurts, have the advantage over the initial raw material (milk) in the production of metabolites in the form of organic acids that prolong their shelf life. Lactic acid bacteria (LAB) can act as probiotics, providing numerous benefits when consumed regularly. This article aimed to quantify the LAB present in yogurts and fermented dairy drinks sold in the Metropolitan Region of Recife (RMR), in Pernambuco. LAB quantification used the pour plate plating technique on MRS Agar and expressed in Colony Forming Unit per gram (CFU g-1). The pH and total acidity of the samples were also determined. None of the 13 yogurt             samples reached the minimum count of 107 CFU g-1 BAL, although the pH values ​​were below 4.5 (3.98 - 4.36). As for the 9 samples of fermented dairy drinks, only 4 samples had LAB concentration below 106 CFU g-1. Except for samples BLF3, BLF7, and BLF8, all fermented dairy drinks complied with the acidity and pH parameters. The evaluation of yoghurts and fermented dairy drinks carried out highlights the need for greater control in production so that the products fit the minimum requirements for the provision of the proposed benefits and greater transparency regarding the information of their respective functional components, promoting a conscious and honest consumption of the population.